2017
DOI: 10.3390/min7100190
|View full text |Cite
|
Sign up to set email alerts
|

The Force of Crystallization and Fracture Propagation during In-Situ Carbonation of Peridotite

Abstract: Subsurface mineralization of CO 2 by injection into (hydro-)fractured peridotites has been proposed as a carbon sequestration method. It is envisaged that the expansion in solid volume associated with the mineralization reaction leads to a build-up of stress, resulting in the opening of further fractures. We performed CO 2 -mineralization experiments on simulated fractures in peridotite materials under confined, hydrothermal conditions, to directly measure the induced stresses. Only one of these experiments re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 66 publications
(104 reference statements)
1
32
0
Order By: Relevance
“…It was submitted to a triaxial loading in order to reach a predefined isotropic stress state of 30 MPa, a stress value representative of in situ serpentinization reactions (Marcaillou, ). The local mechanical properties were adjusted to fit the behavior of the model to the behavior of the peridotite (Van Noort et al, ). These parameters are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was submitted to a triaxial loading in order to reach a predefined isotropic stress state of 30 MPa, a stress value representative of in situ serpentinization reactions (Marcaillou, ). The local mechanical properties were adjusted to fit the behavior of the model to the behavior of the peridotite (Van Noort et al, ). These parameters are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The alteration of elastic properties and strength of rocks undergoing serpentinization has fundamental implications on the mechanical and seismic properties of the lithosphere and has thus to be studied. Typical values of stiffness, uniaxial tensile strength, cohesive shear strength and other mechanical properties of ultramafic rocks are presented in Table (Van Noort et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little work has been done to constrain crystallization pressures in these types of situations (see Ghofrani & Plack, 1993;Ostapenko, 1976;Ostapenko & Yaroshenko, 1975;van Noort et al, 2017;Wolterbeek et al, 2017). However, the role of confined crystallization is of primary importance to the dynamics of numerous geophysical processes, including replacement of olivine by serpentinite or magnesite (Kelemen et al, 2011;Kelemen & Hirth, 2012), reaction-induced fracturing (Kuleci et al, 2017;Zhu et al, 2016), and geologic carbon sequestration (Kelemen & Matter, 2008;Matter & Kelemen, 2009).…”
Section: 1029/2017jb015369mentioning
confidence: 99%
“…Large degrees of serpentinization are commonly observed in the field (Iyer et al, 2008;Macdonald & Fyfe, 1985) and can be reproduced by numerical models of olivine hydration that include fracturing processes (e.g., Malvoisin, Podladchikov, et al, 2017;Rudge et al, 2010). However, only a few experimental studies have observed reaction-induced fracturing during hydration reactions (Kuleci et al, 2017;Zhu et al, 2016) and attempts at measuring reaction-induced stresses due to olivine hydration or carbonation have met with limited success (Malvoisin & Brunet, 2014;van Noort et al, 2017…”
Section: Serpentinizationmentioning
confidence: 99%
“…As a result, there is no consensus regarding the nature of deformation due to retrograde metamorphism (e.g., Ghofrani & Plack, 1993;Kuleci et al, 2017;Ostapenko & Yaroshenko, 1975;Skarbek et al, 2018;Van Noort et al, 2017;Wolterbeek et al, 2017;Zhu et al, 2016). Generation of stress due to crystallization has been mostly studied in environments where crystallization occurs within a porous medium whose matrix does not participate in the reaction.…”
Section: Introductionmentioning
confidence: 99%